Body in Flight - Settimio, Samantha (East Carolina University, 2013)
This master's thesis is a collection of poetry focusing on the emotional and behavioral responses of a woman whose perception of life is considerably twisted by her chances at inheriting cancer and certain romantic proclivities and preferences. In this collection, the narrator considers her potentially quite young death by cancer, pursues an alternative lifestyle, and cautiously considers the lives of any children she may have. This collection is heavily "of the body" in that it speaks of issues such as death and love through the physical. This is intended as a representation of how the speaker has coped with her lack of control. This collection, however, would be incomplete to simply have a woman face death and decide to (alternatively enough) live her life to the fullest. More so, it seeks to consider questions of that life: How does a woman face imminent death when she knows the only reason she will die is because she was born female? How, then, does she relate to her body? How does it affect relationships with her mother and lovers? Perhaps some of the answers (and further questions) lie in the fact that she embraces polyamory, engages in multiple coexisting, intimate relationships, within which there is little time to waste on jealousy or pettiness. These poems trace the relationship of a person to her body and watch as she negotiates that body with others.
Keywords: Fine arts; Matrilineage; Poetry; Polyamory; Human body--Poetry; Death--Poetry